Heterogeneous Isomorphism Principles in Cultural Linguistic Methodology (Sinología hispánica. China Studies Review, 2020)
Isomorphism can refer to the same or similar structure between different systems or subject systems, or to the similarity between the internal components of the system and the whole system in a certain way, that is, the corresponding relationship between the parts and the whole. The isomorphism indicates that complex system itself has its universal characteristics and universal rules. The principles of heterogeneous isomorphism apply to the study of language ontology, language and culture, language teaching and other aspects by means of set, analogy and simplification.